Catalytic chemical vapor deposition of large-area uniform two-dimensional molybdenum disulfide using sodium chloride. (23rd October 2017) - Song, Jeong-Gyu; Hee Ryu, Gyeong; Kim, Youngjun; Je Woo, Whang; Yong Ko, Kyung; Kim, Yongsung; Lee, Changseung; Oh, Il-Kwon; Park, Jusang; Lee, Zonghoon; Kim, Hyungjun
Abstract: The effective synthesis of atomically thin molybdenum disulfides (MoS2 ) of high quality and uniformity over a large area is essential for their use in electronic and optical devices. In this work, we synthesize MoS2 that exhibit a high quality and large area uniformity using chemical vapor deposition (CVD) with volatile S organic compound and NaCl catalysts. In the latter process, the NaCl enhances the growth rate (5 min for synthesis of monolayer MoS2 ) and purity of the synthesized MoS2 . The optical microscopy, Raman spectroscopy, x-ray photoemission spectroscopy, photoluminescence, and transmission electron microscopy measurements indicate that the NaCl-CVD MoS2 has a large grain size, clear Raman shift, strong photoluminescence, good stoichiometry, and 6-fold coordination symmetry. Moreover, we demonstrate that the electron mobility (10.4 cm 2 V −1 s −1 ) and on/off current ratio (3 × 10 7 ) of monolayer MoS2 measured using a field-effect transistor are comparable to those of previously reported MoS2 synthesized using CVD.